Interdisciplinary perspectives on conservation and culture - Yuniawan Isyanto, Agus; Fatimah, Ai Tusi; Thoyyibah, Luthfiyatun; Millah, Ana Samiatul (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
This article describes conservation and cultural perspectives from various disciplines based on research from various disciplines. The description is categorized into three parts; conservation and culture of applied science and health, conservation and culture of social science and humanity, conservation and culture of business and entrepreneurship. Natural sciences, health, social humanities, business, and entrepreneurship have all contributed to the conservation of natural resources and the environment, according to the results of journal article searches. Conservation in applied science promotes environmental, water, agricultural, biodiversity, and wildlife conservation, as well as land preservation and building reuse. Conservation can be accomplished through management and strategies derived from indigenous peoples' traditions with implications for nature conservation. The use of environmentally friendly health infrastructure is part of conservation in the health sector. Conservation is the study of the relationship between human interaction and the environment in a society in order to achieve a better life in the field of social sciences and humanities. Conservation strategy, policy, and education are important studies on conservation issues in the social sciences and humanities. Furthermore, conservation strategies are critical for identifying efficiency and conservation in support of development integration and disaster mitigation. Conservation and local wisdom-based education is a learning process that aims to raise environmental and cultural awareness and concern. In particular, conservation and local wisdom-based entrepreneurship education is a promising topic to be studied and researched further to generate various businesses that support environmental and cultural preservation.